Sublingual flagellin protects against acute pneumococcal pneumonia in a TLR5-dependent and NLRC4-independent fashion. (September 2016) - Muñoz-Wolf, Natalia; Rial, Analía; Fougeron, Delphine; Tabareau, Julien; Sirard, Jean-Claude; Chabalgoity, José A
Aim: To evaluate efficacy of sublingual flagellin to treat acute pneumonia.Materials & methods: Mice were treated sublingually with flagellin and challenged intranasally with a lethal dose of pneumococcus. Flagellins lacking TLR5 or NLRC4 activation domains were used to assess their contribution to protection.Results: Sublingual flagellin protected mice in a TLR5-dependent, NLRC4-independent fashion. Neutrophils were required for protection. Flagellin-stimulated lung epithelial cells recapitulated the lung's transcriptional profile suggesting they could be targeted by flagellin in vivo .Conclusion: Ligation of TLR5, a pathogen recognition receptor not naturally engaged by pneumococcus, protects mice from invasive pneumonia when administered via sublingual route. This can be a highly cost-effective alternative therapy against pneumonia.